Cognitive Perspectives on Early Christology - McClellan, Daniel O. (Biblical interpretation, 2017)
Central to all christological models are concepts of agency, identity, and divinity, but few scholars have directly addressed these frameworks within their ancient West Asian contexts. Rather, the proclivity has been to retroject modern, Eurocentric, and binary frameworks onto the ancient texts, resulting in christological models that inevitably reflect modern orthodoxies and ontological categories. The future of christological research will depend on moving beyond this tendentiousness. In an effort to begin this process, this paper will apply findings from the cognitive sciences – which examine the way the human brain structures its perception of the world around it – to the reconstruction of ancient frameworks of agency, identity, and divinity. Applying these findings to early Jewish literature reveals the intuitive conceptualization of God’s agency, reified as the divine name, as a communicable vehicle of divine presence and authority. These observations support the conclusion that early Jewish conceptualizations of divine agency provided a conceptual template for the development of early christology.